PREDIKSI PENJUALAN OBAT PADA RUMAH SAKIT MENGGUNAKAN METODE DOUBLE EKSPONENTIAL SMOOTHING - Winda Yoceva Pane; Nathanael Chrisman Laurentio Pardede; Rikky Martua Hasudungan Simaremare; Evta Indra (Politeknik Bisnis Indonesia, 2024)
Royal Prima Hospital faces challenges in managing its drug inventory. Each month, the available quantity of drugs remains the same without considering the actual needs, based only on the amount of drugs sold. As a result, there is often an excess of drug stock, leading to reduced shelf life, lower drug prices, and unsatisfactory patient service. This situation is certainly detrimental to the hospital. To help hospital management reduce errors in forecasting drug sales, the Double Exponential Smoothing forecasting method with an alpha of 0.6 was applied, as the sales data show a trend. This method provides a solution that can be used to predict the number of drugs that will be sold in both the short and long term with a high level of accuracy. The forecasting results produced a Mean Absolute Error (MAE) of 791.64, a Mean Square Error (MSE) of 17,887,289,511.31, and a Mean Absolute Percentage Error (MAPE) of 0.78%. Thus, hospital management can manage drug inventory more efficiently and reduce wastage. This study offers significant benefits by providing a more accurate approach to forecasting drug sales.